Breast Reconstruction in Inflammatory Breast Cancer: An Analysis of Predictors, Trends, and Survival from the National Cancer Database - Murad J. Karadsheh, MD; Jacob Y. Katsnelson, MD; Karen J. Ruth, MS; Eric S. Weiss, MD; James C. Krupp, MD; Elin R. Sigurdson, MD; Richard J. Bleicher, MD; Marilyn Ng, MD; M. Shuja Shafqat, MD; Sameer A. Patel, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2021)
Introduction:. Survival for women diagnosed with inflammatory breast cancer (IBC) has improved with advances in multimodal therapy. This study was performed to evaluate trends, predictors, and survival for reconstruction in IBC patients in the United States. Methods:. Women who underwent mastectomy with or without reconstruction for IBC between 2004 and 2016 were included from the National Cancer Database. Predictors for undergoing reconstruction and association with overall survival were determined. Results:. Of 12,544 patients with IBC who underwent mastectomy, 1307 underwent reconstruction. Predictors of reconstruction included younger age, private insurance, higher income, performance of contralateral prophylactic mastectomy, and location within a metropolitan area (P < 0.001). The proportion of women having reconstruction for IBC increased from 7.3% to 12.3% from 2004 to 2016. Median unadjusted overall survival was higher in the reconstructive group l [93.7 months, 95% confidence interval (CI) 75.2–117.5] than the nonreconstructive group (68.1 months, 95% CI 65.5–71.7, hazard ratio = 0.79 95% CI 0.72–0.88, P < 0.001). With adjustment for covariates, differences in overall mortality were not significant, with hazard ratio of 0.95 (95% CI 0.85–1.06, P = 0.37). Conclusions:. Reconstruction rates for IBC are increasing. Women with IBC who undergo reconstruction tend to be younger and are not at the increased risk of all-cause mortality compared to those not having reconstruction. The National Cancer Database does not differentiate immediate from delayed reconstruction. However, the outcomes of immediate reconstruction in carefully selected patients with IBC should be further studied to evaluate its safety. This could impact current guidelines, which are based largely on an expert opinion.